SPREAD OF ULCERS OF THE TONGUE IN CATTLE FARMS IN CENTRAL UKRAINE - Канівець, Н. С. (Scientific Progress & Innovations, 2014)
The question of spreading of the tongue ulcers in cattle farms in the central region of Ukraine is explored in our article. As a result, product reviews slaughter found that in some farms of the Poltava region are affected nearly 32,6% of the animals. In Kotel’va, Reshetylivka, Chornuhy, Shyshaky districts of Poltava Region tongue ulcer registered between 15 and 37 %. In regions of Sumy, Cherkasy and Kharkiv – 17–42 %. Obtained data show a significant spreading of tongue ulcers in cattle in the investigated region.